Impact of Nonlinear Power Amplifier on BER Performance of OTFS Modulation - Sharma S.; Singh A.; Deka K.; Adjih C. (My University, 2025)
Recently, two dimensional orthogonal time frequency space (OTFS) modulation technique has introduced in wireless communications to combat the effects of multipath fading and Doppler spread. In this paper, we analyze the impact of nonlinear power amplifier (NPA) and phase noise on the OTFS system over the EVA channel model. The study focuses on the bit error rate (BER) performance concerning the input-back-off (IBO) and the nonlinearity parameter values of the NPA. The results demonstrate that both NPA and phase noise significantly degrade the OTFS system performance, especially for higher modulation schemes and low values of IBO. Furthermore, we numerically analyze the impact of system parameter variations on BER performance. © 2023 IEEE.